2018
DOI: 10.1016/j.jmps.2018.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Vibrations and elastic waves in chiral multi-structures

Abstract: We develop a new asymptotic model of the dynamic interaction between an elastic structure and a system of gyroscopic spinners that make the overall multi-structure chiral. An important result is the derivation and analysis of effective chiral boundary conditions describing the interaction between an elastic beam and a gyroscopic spinner. These conditions are applied to the analysis of waves in systems of beams connected by gyroscopic spinners. A new asymptotic and physical interpretation of the notion of a Ray… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(61 citation statements)
references
References 42 publications
0
61
0
Order By: Relevance
“…For this reason, the theory of gyro-elastic continua has been developed in the literature (see, for example, [41,42]). Recently, attaching gyroscopic spinners to elastic beams in order to modify the dynamic properties of the beams has been proposed in [43,44] and creating novel low-frequency resonators for seismic applications has been discussed in [45].…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, the theory of gyro-elastic continua has been developed in the literature (see, for example, [41,42]). Recently, attaching gyroscopic spinners to elastic beams in order to modify the dynamic properties of the beams has been proposed in [43,44] and creating novel low-frequency resonators for seismic applications has been discussed in [45].…”
Section: Introductionmentioning
confidence: 99%
“…Each spinner is a solid of revolution having mass m , moment of inertia I 1 about its axis of revolution and moment of inertia I 0 about the two transverse axes with origins at the spinner's base. Another important characteristic of the spinners is the gyricity italicΩ=ψ˙+ϕ˙, which is the sum of the spinner's spin rate ψ˙ and precession rate ϕ˙ [8,9]. In [8,9], it has been shown that the gyricity is constant under the assumption of small nutation angle.…”
Section: Spectral Problem For a Finite System Of Beams Connected By Gmentioning
confidence: 99%
“…Recently, a linearized formulation has been proposed to replace the spinner connected to the end of an elastic beam with effective boundary conditions, both when the beam end is hinged [8] and when it is free [9]. In [8,9], it was shown that the eigenfrequencies of an elastic beam can be tuned by changing the gyricity of the spinner, and that flexural waves are coupled with rotational motion.…”
Section: Introductionmentioning
confidence: 99%
“…From the linear equation (39) it is evident that the analysis developed for System (II) also includes, as particular cases, that for System (0) (by considering V…”
Section: Bloch-floquet Analysis and Resonancementioning
confidence: 99%
“…For this reason, such longitudinal vibrations are referred to as nested Bloch waves, as they are 'nested' to the transverse ones. Indeed, while the classical Bloch longitudinal waves (in System (0)) have frequency defined by eqn (52) and undefined amplitude, the nested Bloch longitudinal waves have frequency defined by relation (35) and amplitude defined in relation of the transverse oscillations amplitudes V [0] AC1 and V [0] BC1 via the linear system (39). It is also worth to remark that in the presence of transverse vibrations, longitudinal vibrations may become possible at frequencies that are forbidden in the absence of flexural motion.…”
Section: Purely Axial Vibrations: System (0)mentioning
confidence: 99%